Three-dimensional progressive collapse analysis of reinforced concrete frame structures subjected to sequential column removal. (1st February 2017) - Arshian, Amir Hossein; Morgenthal, Guido
Highlights: The alternate path mechanism in RC structures is studied for extreme initial damage. A numerical frame-work is proposed for sequential column-removal scenarios. Removal sequence of columns significantly influences the 3D redistribution of forces. Sequential column removal may induce larger section forces than the simultaneous one. A feasible strengthening technique is studied for activating the catenary mechanism. Abstract: In the last decade, a great care is exercised in progressive collapse analysis of structures to avoid the catastrophic consequences of such a system-level problem. The majority of the previous research works dealt with the quantification of resisting mechanisms such as the compressive arching action using two-dimensional frameworks. The three-dimensional (3D) studies are also limited to considering the initial damage as instantaneous removal of one or simultaneous removal of multiple supporting elements. This paper studies the 3D nonlinear dynamic response of reinforced concrete structures subjected to sequential column removal scenarios. A sequential nonlinear time-history analysis algorithm alongside with a macro modeling approach is utilized to predict the dynamic redistribution of the gravity loads. The efficiency of such a numerical framework is verified through comparison of computational results with the available experimental data from a past 3D half-scale test. Good agreement is observed for the global and for the local response quantities. Furthermore, a practical strengthening technique is applied into the computational model of the structural system for artificially activating the catenary mechanism. Analysis results show that strengthening of peripheral beams with externally bonded steel plates significantly increases the rotational ductility at beam-sections and in turn, enables the damaged structure to accommodate larger deformations. Finally, the influence of the removal sequence on the 3D force redistribution mechanism is investigated. Permanent plastic deformations and maximum sectional forces of a sequential removal scenario are found to be larger on average compared with those obtained from an at-once removal scenario. It is demonstrated that the time-lag between the column removals considerably affects the 3D redistribution of gravity loads, and shall not be neglected in case of considering an extreme initial damage.